The Effect of Compensation Suitability, Situational Leadership Style, Effectiveness of the Supervisory Board and Tri Hita Karana Culture on The Tendency of Fraud in LPD - Ni Ketut Rasmini (International Journal of Social Science and Business, 2023)
The tendency of fraud in LPD during the Covid-19 Pandemic is often caused by several factors. Based on this, this study aims to analyze the effect of compensation suitability, situational leadership style, effectiveness of the supervisory board, and Tri Hita Karana culture on the tendency of fraud in LPD in the era of the Covid-19 Pandemic. The study was conducted with the object of LPD in Gianyar Regency, because it refers to Bali Province LPLPD data which shows indications of the highest level of health problems in Gianyar Regency. Samples were taken by the Slovin method, from 270 populations 161 LPD samples were obtained. Data were collected by survey method and using respondents from management, supervisory board, and employees of the finance department in each LPD sample. Of the 483 questionnaires distributed, 385 (79.71%) were returned and 377 were used (97.92%). Data were analyzed using Multiple Regression Test. The test results showed that the effectiveness of the supervisory board, situational leadership style, and Tri Hita Karana culture had a negative and negative effect on the tendency of fraud in LPD in the COVID-19 Pandemic Era, while the suitability of compensation did not affect the tendency of fraud in LPD in the COVID-19 Pandemic Era. This shows the importance of the role of supervisory bodies, situational leadership style and Tri Hita Karana culture in fraud prevention in LPD.